The Influence of Moral Reasoning, Collectivism, And Retaliation Against the Intention of Whistleblowing (A Case Study on Bank Nagari) - Faradilla, Yosi Aunia; Djefris, Dedy; Surya, Firman; Santi, Elfitri (Economics, Business, Accounting & Society Review, 2023)
Nowadays, the term whistleblowing has often been discussed in the wider community, it is because of the many acts of fraud that have been revealed both in companies and agencies. One of the fraud cases that often occurs is in the banking sector. This study aims to determine and analyze the influence of moral reasoning, collectivism, and retaliation on the intention of whistleblowing at PT Bank Nagari Padang Main Branch. The research method used is a quantitative approach. The population in this study is employees of PT Bank Nagari Main Branch of Padang. The sampling technique was carried out by purposive sampling method with a total of 135 respondents. The data collection in this study was using questionnaires distributed to employees of PT Bank Nagari Padang Main Branch. Data is processed using SPSS v.25 application. The results showed that moral reasoning had no effect on the intention to whistleblow, collectivism had a positive effect on the intention to whistleblow, and retaliation had a negative effect on the intention to whistleblow.